2018
DOI: 10.1177/1368430218755922
|View full text |Cite
|
Sign up to set email alerts
|

Social and biological intergroup hierarchy beliefs: A cross-cultural comparison between the US and South Korea

Abstract: The present research investigated social and biological intergroup hierarchy beliefs in the US and South Korea, representative Northern European-heritage and East Asian cultures, respectively. We hypothesized that individual-orientation (the emphasis on individuals and individual achievements) and group-orientation (the emphasis on groups and efficient functioning of groups) would predict social and biological hierarchy beliefs differently within and between these cultures. As expected, intergroup hierarchy be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…We believe these findings provide the first empirical and neural evidence for the novel theoretical framework that SC in the social hierarchy can be best understood as a means of minimizing the metabolic cost of the body (Constant et al, 2019;Theriault et al, 2021), which can contribute to building a novel framework for understanding the complex motivations underlying strategic social conformity. Given that the behavioral and neural processing of social hierarchy can be influenced by cultural differences (Freeman et al, 2009;Chiao, 2010;Shin et al, 2019), it is essential for future research to investigate whether the tendency of strategic conformity in social hierarchical context can be replicated in other cultural contexts such as European and Western cultures.…”
Section: Discussionmentioning
confidence: 99%
“…We believe these findings provide the first empirical and neural evidence for the novel theoretical framework that SC in the social hierarchy can be best understood as a means of minimizing the metabolic cost of the body (Constant et al, 2019;Theriault et al, 2021), which can contribute to building a novel framework for understanding the complex motivations underlying strategic social conformity. Given that the behavioral and neural processing of social hierarchy can be influenced by cultural differences (Freeman et al, 2009;Chiao, 2010;Shin et al, 2019), it is essential for future research to investigate whether the tendency of strategic conformity in social hierarchical context can be replicated in other cultural contexts such as European and Western cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Stratified DHs can result from group-based productivity differences. However, they can also follow from group-based discrimination (Henrich and Boyd, 2008) or segregation (Tsvetkova et al, 2018) like in caste and class systems or intergroup hierarchy beliefs (Shin et al, 2018). In stratified DHs, communication and interaction are rather inside than between the layers and secondary communication is not allowed.…”
Section: The Social Structuresmentioning
confidence: 99%
“…Previous research has found that perceiving “foreignness” as a negative quality predicted prejudice toward immigrants and foreign workers (Mullen, ). In the current study, we examined responses to both socially‐ and biologically‐based differences , because norms and values may differentially affect the impact of a socially‐ or biologically‐based difference (Rangel & Keller, ; Shin, Dovidio, Napier, Stangor, & Uleman, ). Lay theories often portray race (e.g., White, Black, or Asian) as biologically‐based, whereas ethnicity (e.g., French or Japanese) is primarily related to culture (involving, for example, language, religion, and/or traditions).…”
Section: Predictors Of Prejudice Toward Immigrants and Foreign Workersmentioning
confidence: 99%